A structural study of the capsular antigens of escherichia coli K36 and klebiella K68 - Stanley, Shawn Mark Ross (Rhodes University, Faculty of Pharmacy, Pharmacy, 1987)
From Introduction: Bacterial cells all have a cytoplasmic membrane (see Figure 1) which regulates the movement of ions and molecules into and out of the bacterium. Enclosing this membrane is a cell wall of which there are two general types, which are differentiated by the Gram stain(02) as being either gram positive or gram negative (depending upon whether they hold the gram stain after washing with ethanol). The cell wall provides the cell with shape and rigidity and is composed, in the case of gram positive types, of peptidoglycan, and in the case of gram negative bacteria, of a peptidoglycan and an outer membrane (see Figure 2). The peptidoglycan layer, common to both cell wall types, consists of a backbone of alternating units of N-acetylglucosamine and N-acetylmuramic acid to which peptides are attached by amide links. This heteropolymer is a highly cross linked mosaic and this gives it strength and rigidity. In gram positive bacteria, this layer also contains two carbohydr ate antigens, a simple polysaccharide and a teichoic acid; these are usually the type specific or major group antigens of the bacterium. Many of the bacteria also produce exopolysaccharides (see Figure 3) either as discrete capsules (for example, the Enterobacteriaceae K antigens) or unattached slime layers (for example, the Enterobacteriaceae M antigens). The vast majority of these polysaccharides are heteroglycans(03) composed of contiguous oligosaccharide repeating units. Their monosaccharide components are largely neutral hexoses, 6-deoxy hexoses and also amino sugars. (03) Pentose units are rare. (03) The capsular polysaccharides usually have a high content of acidic constituents such as uronic acids, phosphate groups, or pyruvate ketals. (01),KMBT_363,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Enterobacteriaceae; Klebsiella; Escherichia; Antigens